Effects of compound probiotics on growth performance, immunity, antioxidant capacity and gut microbiota in weaned rabbits - Ye, Changchuan; Shi, Menglei; Ren, Jingnan; Zhang, Yan; Zhang, Yeqiu; Zhang, Yingmei; Du, Yifei; Wang, Xinyi; Liu, Qinghua (Frontiers in Veterinary Science, 2025)
IntroductionIn modern intensive animal husbandry, weaned rabbits frequently face disrupted intestinal barrier function and impaired weight gain which triggered by weaning stress. To solve this problem sustainably, innovative and effective nutritional regulation strategies should be developed. As feed additives, compound probiotics could improve feed conversion ratio and animal intestinal health and thus gain increasing recognition. Three dominant strains (Lactobacillus plantarum QZF, Bacillus velezensis BD and Cyberlindnera fabianii EMS) were isolated from silage and combined to form different compound probiotics. In this study, we evaluated the effect of compound probiotic on growth performance, immune function, antioxidant capacity and intestinal microbiota in weaned rabbits.MethodsA total of 64 weaned New Zealand rabbits were randomly divided into four groups. The CON group was fed a basal diet. Three treatment groups were established by supplying the following probiotics: SP Group, L. plantarum QZF (108 CFU/d); DP1 Group, L. plantarum QZF (108 CFU/d) and C. fabianii EMS (107 CFU/d); DP2 Group: L. plantarum QZF (108 CFU/d) and B. velezensis BD (108 CFU/d).Results and discussionOur results showed that dietary supplementation with probiotic significantly promoted growth performance (e.g., increased average daily gain and decreased feed-to-gain ratio), enhanced immune function (reflected by elevated plasmic immunoglobulin levels and reduced pro-inflammatory cytokine concentrations) and improved antioxidant capacity (manifested by higher activities of superoxide dismutase and glutathione peroxidase and lower malondialdehyde content) in weaned rabbits. Furthermore, compound probiotic supplementation influenced the composition of intestinal microflora by decreasing the abundance of Fusobacteriota (disease-related) and increasing the abundance of Christensenellaceae_R-7_group. Supplementation with compound probiotic can alter the abundance of specific gut microbiota to maintain a healthy microbial community. In conclusion, this study demonstrates that probiotics (especially compound probiotics) serve as a valuable nutritional strategy for alleviating weaning stress, optimizing growth performance and maintaining intestinal microbiota homeostasis in weaned rabbits, providing theoretical support for the application of compound probiotics in rabbit production